2013
DOI: 10.1074/jbc.m113.470260
|View full text |Cite
|
Sign up to set email alerts
|

RanBPM Protein Acts as a Negative Regulator of BLT2 Receptor to Attenuate BLT2-mediated Cell Motility

Abstract: Background:The regulatory mechanism of BLT2 is largely unknown. Results: RanBPM interacts with BLT2 and inhibits BLT2-induced ROS generation and chemotaxis. Conclusion: Our findings suggest that RanBPM acts as a negative regulator of BLT2. Significance: Identification of regulators would provide better understanding of BLT2 signaling and potentially various BLT2-associated inflammatory pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Screening a human thymus cDNA to identify BLT 2 receptor‐interacting proteins recently identified that RanBPM, a member of the Ran‐GTPase‐binding protein family, which can bind at the C‐terminal of the BLT 2 receptor in the absence of LTB 4 , whereas the co‐localization of these proteins was abolished in the presence of LTB 4 (Wei et al ., ). RanBPM overexpression attenuated, whereas knock‐down promoted, BLT 2 receptor‐mediated motility and generation of ROS in response to either LTB 4 or 12HHT (Wei et al ., ), suggesting that RanBPM may act as a negative regulator of BLT 2 receptor signalling in cell motility. Finally, the BLT 2 receptor dissociation from RanBPM was dependent on phosphorylation of BLT 2 receptors at Thr 355 , a site previously identified by the same investigators as critical for LTB 4 ‐induced BLT 2 receptor‐mediated chemotaxis through PI3K‐Akt signalling (Wei et al ., ).…”
Section: Blt Receptorsmentioning
confidence: 97%
“…Screening a human thymus cDNA to identify BLT 2 receptor‐interacting proteins recently identified that RanBPM, a member of the Ran‐GTPase‐binding protein family, which can bind at the C‐terminal of the BLT 2 receptor in the absence of LTB 4 , whereas the co‐localization of these proteins was abolished in the presence of LTB 4 (Wei et al ., ). RanBPM overexpression attenuated, whereas knock‐down promoted, BLT 2 receptor‐mediated motility and generation of ROS in response to either LTB 4 or 12HHT (Wei et al ., ), suggesting that RanBPM may act as a negative regulator of BLT 2 receptor signalling in cell motility. Finally, the BLT 2 receptor dissociation from RanBPM was dependent on phosphorylation of BLT 2 receptors at Thr 355 , a site previously identified by the same investigators as critical for LTB 4 ‐induced BLT 2 receptor‐mediated chemotaxis through PI3K‐Akt signalling (Wei et al ., ).…”
Section: Blt Receptorsmentioning
confidence: 97%
“…Previously, the concentration of the BLT2 ligands used for chemotaxis experiments in CHO-BLT2 cells was 100–300 n M , and low doses, such as 10 n M , showed no significant effects in these BLT2-expressing cells. 16 , 26 , 29 Thus, we defined the 10 n M concentration as the low-dose ligand condition. As shown in Figure 2a , the BLT2 ligand LTB 4 -enhanced chemotaxis in cells expressing BLT2 D196G compared with cells expressing wild-type BLT2 under low-dose conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that the activation of BLT2 induces the generation of intracellular ROS which, in turn, plays a critical role in cell motility. 15 , 16 , 26 Therefore, we determined whether BLT2 D196G leads to enhanced ROS generation. Enhanced LTB 4 -elicited ROS generation was clearly observed in cells transfected with BLT2 D196G ( Figures 4a and b ) under low-dose ligand conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations